Effects of Antimycin and its Neutralizing Agent, Potassium Permanganate, on Aquatic Macroinvertebrates in a Great Smoky Mountains National Park Watershed. (2nd December 2015) - Gibbs, W. Keith; Kulp, Matt A.; Moore, Steve E.; Cook, S. Bradford
Abstract: We assessed the effects of antimycin (Fintrol) on benthic macroinvertebrates during a large Brook Trout Salvelinus fontinalis restoration project in the southeastern United States. Control and treatment sites were established in first‐ through fourth‐order streams throughout the watershed and below the fish passage barrier where a neutralizing agent (potassium permanganate [KMnO4 ]) was administered. Hess samples were collected before and after chemical application (short term: 1 and 2 months after; long term: 9 and 12 months after). Analysis of similarity, nonmetric multidimensional scaling, and repeated‐measures ANOVA were used to determine differences in assemblage metrics among control, treatment, and neutralization sites over time. Macroinvertebrate communities and their responses to antimycin were different at downstream (third‐ and fourth‐order) sites relative to headwater (first‐ and second‐order) sites. Overall, abundances (especially stonefly and caddisfly abundances) increased after antimycin application, reflecting a positive response within the macroinvertebrate assemblage. Several variables, including mayfly and stonefly abundances, were significantly different among control, concentrated‐KMnO4, and dilute‐KMnO4 sites; however, differences were undetectable after 9 months. Many taxa were substantially more abundant several months after treatment, indicating a thriving macroinvertebrate assemblage throughout the watershed. Future studies yielding similar results would suggest that native fish stocking efforts can commence shortly after chemical degradation. Received May 2, 2014; accepted September 10, 2015